2010
DOI: 10.1002/chem.201000320
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide(III) Complexes of 4,10‐Bis(phosphonomethyl)‐1,4,7,10‐tetraazacyclododecane‐1,7‐diacetic acid (trans‐H6do2a2p) in Solution and in the Solid State: Structural Studies Along the Series

Abstract: Complexes of 4,10-bis(phosphonomethyl)-1,4,7,10-tetraazacyclododecane-1,7-diacetic acid (trans-H(6)do2a2p, H(6)L) with transition metal and lanthanide(III) ions were investigated. The stability constant values of the divalent and trivalent metal-ion complexes are between the corresponding values of H(4)dota and H(8)dotp complexes, as a consequence of the ligand basicity. The solid-state structures of the ligand and of nine lanthanide(III) complexes were determined by X-ray diffraction. All the complexes are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 98 publications
(157 reference statements)
3
26
0
Order By: Relevance
“…The structures of the Ln(trans-DO2A2P) 3− complexes (trans-DO2A2P (Chart 5.10) is the transbisphosphonate analog of DOTA) have been studied by various techniques [313,391,392]. Relaxometric and 17 O NMR studies have shown that the Gd 3+ chelate adopts a TSA coordination geometry, with q = 0 [391].…”
Section: Phosphinates and Phosphonate Estersmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of the Ln(trans-DO2A2P) 3− complexes (trans-DO2A2P (Chart 5.10) is the transbisphosphonate analog of DOTA) have been studied by various techniques [313,391,392]. Relaxometric and 17 O NMR studies have shown that the Gd 3+ chelate adopts a TSA coordination geometry, with q = 0 [391].…”
Section: Phosphinates and Phosphonate Estersmentioning
confidence: 99%
“…Relaxometric and 17 O NMR studies have shown that the Gd 3+ chelate adopts a TSA coordination geometry, with q = 0 [391]. X-ray studies of the DO2A2P complexes along the lanthanide series have shown that the TSA coordination geometry is present for the larger ions (Ln = Ce-Sm), and the TSA for the smaller ones (Ln = Sm-Yb) [392]. PCS shifts for the paramagnetic complexes (except Gd) were rationalized on the basis of the Ce 3+ and Yb 3+ complexes, as models of the TSA and TSA geometries, giving calculated structures in agreement with the solid-sate structures.…”
Section: Phosphinates and Phosphonate Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyaza macrocycles with appended methylphosphonate groups usually present very high values for the first protonation constant(s), which can hinder the accurate determination of their value(s) by potentiometry, as previously observed. [13,18,[20][21][22][23][24][25][26] This trend has been explained by the effect of spreading the high electron density of the fully deprotonated phosphonate group to the nearest nitrogen atom, [3] or by the formation of strong intramolecular hydrogen bonds. [21] In the case of H 7 te3p1a, the first two protonations have very high values and only an overall constant that corresponds to this double protonation could be determined by the 31 P NMR spectroscopic titration in the alkaline region (pH [9][10][11][12][13][14]; the measurement was performed in an aqueous solution and the ionic strength was maintained at 0.50 mol dm -3 with [N(CH 3 ) 4 ]NO 3 .…”
Section: Acid-base Behaviourmentioning
confidence: 94%
“…The interpretation of the 31 P NMR spectroscopic chemical shift changes is still mostly empirical as different classes of phosphorus compounds show diverse behaviour. However, a significant amount of data has been published with respect to the aminoalkylphosphonate groups in acyclic [28][29][30][31] and macrocyclic [13,[20][21][22]25,26,[32][33][34][35] compounds. In the 31 P NMR spectroscopic titration of H 7 te3p1a, one of the resonances (δ a ) shows a different pH dependence from those of the other two signals (δ b and δ bЈ ).…”
Section: Acid-base Behaviourmentioning
confidence: 99%